What Determines the Quality of Rehabilitation Clinical Practice Guidelines?: An Overview Study. (August 2021) - Dijkers, Marcel P.; Ward, Irene; Annaswamy, Thiru; Dedrick, Devin; Hoffecker, Lilian; Millis, Scott R.
Abstract : Objective: The aim of the study was to determine what factors determine the quality of rehabilitation clinical practice guidelines. Design: Six databases were searched for articles that had applied the Appraisal of Guidelines for Research & Evaluation II quality assessment tool to rehabilitation clinical practice guidelines. The 573 deduplicated abstracts were independently screened by two authors, resulting in 81 articles, the full texts of which were independently screened by two authors for Appraisal of Guidelines for Research & Evaluation II application to rehabilitation clinical practice guidelines, resulting in a final selection of 40 reviews appraising 504 clinical practice guidelines. Data were extracted from these by one author and checked by a second. Data on each clinical practice guideline included the six Appraisal of Guidelines for Research & Evaluation II domain scores, as well as the two Appraisal of Guidelines for Research & Evaluation II global evaluations. Results: All six Appraisal of Guidelines for Research & Evaluation II domain scores were statistically significant predictors of overall clinical practice guideline quality rating; D3 (rigor of development) was the strongest and D1 (scope and purpose) the weakest (overall model P < 0.001, R 2 = 0.53). Five of the six domain scores were significant predictors of the clinical practice guideline use recommendation, with D3 the strongest predictor and D5 (applicability) the weakest (overall model P < 0.001, pseudo R 2 = 0.53). Conclusions: Quality of rehabilitation clinical practice guidelines may be improved by addressing key domains such as rigor of development. Abstract : Supplemental digital content is available in the text.